DNA Damage Potential of Engine Emissions Measured In Vitro by Micronucleus Test in Human Bronchial Epithelial Cells. (6th January 2017) - Cervena, Tereza; Rossnerova, Andrea; Sikorova, Jitka; Beranek, Vit; Vojtisek‐Lom, Michal; Ciganek, Miroslav; Topinka, Jan; Rossner, Pavel
Abstract: Internal combustion engine emissions belong among the major anthropogenic sources of air pollution in urban areas. According to the International Agency for Research on Cancer, there is sufficient evidence of the carcinogenicity of diesel exhaust in human beings. Although alternative fuels, mainly biodiesel, have recently become popular, little is still known about the genotoxicity of emissions from these fuels. We analysed DNA damage expressed as the frequency of micronuclei (MN) in human bronchial epithelial cells (BEAS‐2B), induced by extractable organic matter (EOM; tested concentrations: 1, 10 and 25 μg/ml) obtained from particle emissions from various blends of biodiesel with diesel fuels (including neat diesel fuel (B0), a blend of 70% B0 and 30% biodiesel (B30) and neat biodiesel (B100)). We also tested the effect of selected diesel exhaust organic/genotoxic components [benzo[a]pyrene (B[a]P) concentrations: 25, 100 and 200 μM; 1‐nitropyrene (1‐NP) concentrations: 1, 5 and 10 μM; 3‐nitrobenzanthrone (3‐NBA) concentrations: 1, 5 and 50 μM]. The cells were treated with the compounds for 28 and 48 hr. Our results showed that most of the tested compounds (except for the 25 μM B[a]P, 28‐hr treatment) significantly increased MN frequency. The genotoxicity of EOMs from the engine emissions of diesel and biodiesel engines was comparable. Both nitro‐PAH compounds demonstrated higher genotoxic potential in comparison with B[a]P. Considering our results and due to increasing popularity of alternative fuels, it is prudent that the potential genotoxic effects of various fuels are investigated across engine technologies and operating conditions in a relevant model system.